2017
DOI: 10.1007/s00122-017-2957-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping reveals a rich genetic architecture of stripe rust resistance loci in emmer wheat (Triticum turgidum ssp. dicoccum)

Abstract: Key message SNP-based genome scanning in worldwide domesticated emmer germplasm showed high genetic diversity, rapid linkage disequilibrium decay and 51 loci for stripe rust resistance, a large proportion of which were novel. AbstractCultivated emmer wheat (Triticum turgidum ssp. dicoccum), one of the oldest domesticated crops in the world, is a potentially rich reservoir of variation for improvement of resistance/tolerance to biotic and abiotic stresses in wheat. Resistance to stripe rust (Puccinia striiformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 98 publications
3
34
0
Order By: Relevance
“…GWAS have been successfully applied to the identification of MTAs for many important flax agronomic traits (Soto-Cerda et al, 2014b;a;Xie et al, 2017;You et al, 2018c). The effectiveness of GWAS in identifying MTAs for disease resistance traits is exemplified in wheat for fungal diseases such as Fusarium head blight (FHB) (Buerstmayr et al, 2009), leaf and stem rusts (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…GWAS have been successfully applied to the identification of MTAs for many important flax agronomic traits (Soto-Cerda et al, 2014b;a;Xie et al, 2017;You et al, 2018c). The effectiveness of GWAS in identifying MTAs for disease resistance traits is exemplified in wheat for fungal diseases such as Fusarium head blight (FHB) (Buerstmayr et al, 2009), leaf and stem rusts (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a high level of resistance (IT score = 0–3) response appeared at the adult plant stage and a low level of resistance phenotype appeared at the seedling stage. Similarly, a more susceptible response appeared at the seedling stage than at the adult plant stage [ 16 , 27 , 28 , 29 ]. Wheat genotypes were more susceptible to USA stripe rust races compared to Pakistani stripe rust races, where the resistant phenotype response was dominant.…”
Section: Discussionmentioning
confidence: 99%
“…Population structure, based on the Bayesian model, divides the 465 genotypes into three subpopulations (K = 3). Based on the genotype diversity, a different number of subpopulations were reported, as two subpopulations [ 16 ], three subpopulations [ 29 ], six subpopulations [ 32 ], seven subpopulation [ 31 ] and eight subpopulations [ 27 ]. Critical r 2 was used to estimate the extent of the LD decay with the line intersecting the smooth curve [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, GWAS of minor cereals have focused on practical traits, whereas earlier studies tended to focus on the evaluation and potential of using GWAS in each target species. Disease resistance is one of the most commonly targeted traits for GWAS of oat (Montilla-Bascón et al 2015), emmer wheat (Liu et al 2017), and sorghum (Prom et al 2019). To utilize the rich nutrients of minor cereals (e.g., reviewed by Muthamilarasan et al (2016)), several GWAS results for grain ingredients have been reported in sorghum (Rhodes et al 2014), oat (Newell et al 2012), and foxtail millet (Jaiswal et al 2019).…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%